Flavonoids from Artocarpus teysmanii Miq - S, Jamil; H.M, Sirat; I, Jantan; N, Aimi; M, Kitajima, (Malaysian Journal of Science, 2005)
Phytochemical studies on barks of Artocarpus teysmanii Miq. (Moraceae) have resulted in the isolation of four compounds, xanthone-lactone derivative, artonol B 1, furanodihydrobenzoxanthone derivatives, cycloartobiloxanthone 2 and artobiloxanthone 3 and isoprenylated flavone, artonin E 4.